Dataset of statements on policy integration of selected intergovernmental organizations - Tosun, Jale; Peters, B. Guy (Data in Brief, 2018)
This article describes data for 78 intergovernmental organizations (IGOs) working on topics related to energy governance, environmental protection, and the economy. The number of IGOs covered also includes organizations active in other sectors. The point of departure for data construction was the Correlates of War dataset, from which we selected this sample of IGOs. We updated and expanded the empirical information on the IGOs selected by manual coding. Most importantly, we collected the primary law texts of the individual IGOs in order to code whether they commit themselves to environmental policy integration (EPI), climate policy integration (CPI) and/or energy policy integration (EnPI).